PHILOSOPHICAL-DETERMINISTIC ANALYSIS OF PROTECTION OF WOMEN AND GIRLS FROM VIOLENCE IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In this article, in the process of reforms aimed at increasing the efficiency of protecting women from oppression and violence, based on the activation of human capital, solving women's problems, getting them out of difficult situations, increasing their activity in society, providing women with work, giving them the opportunity to earn income with their own work, young people education, the complex and responsible tasks of protecting them from the influence of various destructive currents, the development of human capital in the protection of women from oppression and violence, the socio-philosophical importance of increasing the activity of women, ensuring their rights and freedoms, the directions and possibilities of social reforms in this regard, analysis done